Current transformer performance in high voltage and low voltage systems - Arifin Abd Aziz, Muhammad Khairul (2008)
Current Transformers (CT's) are instrument transformers that are used to supply a reduced value of current to meters, protective relays, and other instruments. Current transformer provide isolation from the high voltage primary, permit grounding of the secondary for safety, and step-down the magnitude of the measured current to a value that can be safely handled by the instruments. It is one of the critical protective devices in a high voltage substation and low voltage switch board. It is used as a sensor to detect faults that will generate signal to trip the protective relay. The performance of current transformer is very important in preventive and predictive maintenance. It can reduce number of injury and minimize system and equipment failure as well as help to reduce the cost. In this work, the method of measuring and testing the electrical characteristics of CT's are first investigated and the experience gained in the measurement and testing are then used to check and verify the characteristics of CT's found the low voltage switchboard of the Electrical Installation lab. The procedures and steps involved in the measurement and testing are reported and discussed in this work. The method of measurement in the low voltage switchboard are also reported and discussed in this work.